2018
DOI: 10.1016/j.ijdevneu.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of environmental enrichment on behavior, stress reactivity and synaptophysin/BDNF expression in hippocampus following early life stress

Abstract: Exposure to environmental enrichment can beneficially influence the behavior and enhance synaptic plasticity. The aim of the present study was to investigate the mediated effects of environmental enrichment on postnatal stress-associated impact with regard to behavior, stress reactivity as well as synaptic plasticity changes in the dorsal hippocampus. Wistar rat pups were submitted to a 3 h maternal separation (MS) protocol during postnatal days 1-21, while another group was left undisturbed. On postnatal day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 167 publications
(206 reference statements)
6
81
2
1
Order By: Relevance
“…This finding is also in contrast to previous studies which reported that MS did not affect performance of spatial learning and memory in the MWM task (Baudin, et al, ; Dandi et al, ; Levy, et al, ). This difference may be due to the strain of rats which were Long Evans (Baudin, et al, ) or Sprague‐Dawley (Levy, et al, ), while Wistar rats were used in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is also in contrast to previous studies which reported that MS did not affect performance of spatial learning and memory in the MWM task (Baudin, et al, ; Dandi et al, ; Levy, et al, ). This difference may be due to the strain of rats which were Long Evans (Baudin, et al, ) or Sprague‐Dawley (Levy, et al, ), while Wistar rats were used in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, different strains of rats may respond differently to stress. Furthermore, the number of training trials cannot be ignored in this discrepancy, which was three trials per day for five consecutive days (Baudin, et al, ), or five trials per day for four days (Levy, et al, ) or four trials per day for four days (Dandi, et al, ). In our study, however, rats were trained for five consecutive days using the 2‐trial‐per‐day regimen in the MWM, which shows good discriminative for learning and memory, as described in our previous studies (Miladi‐Gorji et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the complete absence of social contacts with siblings during of milk nursing period led to an increase in the amount of time spent in open arms [18]. Daily 3-hour separation of the litter from the mother in the first two or three weeks of life, on the contrary, reduced this indicator [19] [20]. In our work, a complete 3-hour social deprivation of pups was performed from the 2 nd to the 8 th day of life.…”
Section: Discussionmentioning
confidence: 99%
“…Further, studies have been carried out to find the regulation of MeCP2 phosphorylation through neuronal activation, which regulate the expression of BDNF. BDNF is a neurotrophic factor that works as neuroprotective [33], regulate synaptic plasticity [34] and memory formation. There was an increase in the level of different DNMTs (DNMT1 and DNMT3b) at the mRNA as well as protein level in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%